A histomorphological study of central nervous system tumors in pediatric age group at tertiary care teaching hospital - Patel, Bansri B.; Parmar, Dhruv R.; Patel, Shreyas D. (International Journal of Research in Medical Sciences, 2026)
Background: Central nervous system (CNS) tumors are the second most common malignancies in children after acute lymphoblastic leukemia and constitute a significant cause of morbidity and mortality. Their histopathological classification is essential for diagnosis, treatment planning and prognostication. The present study was undertaken to evaluate the histomorphological spectrum of pediatric CNS tumors in a tertiary care teaching hospital. Methods: A retrospective observational study was conducted in the Department of Pathology, B. J. Medical College and tertiary care teaching hospital, Ahmedabad, from March 2022 to July 2024. A total of 100 CNS biopsy specimens from pediatric patients aged 0-12 years were included. Clinical, demographic, radiological and histopathological data were collected and analyzed. Tumors were classified and graded according to histomorphological features. Results: Among the 100 cases studied, males constituted 59% and females 41%, with a male-to-female ratio of 1.4:1. The highest number of cases (34%) occurred in the 0-4 years age group. Supratentorial tumors accounted for 54% of cases, followed by infratentorial tumors (40%) and spinal tumors (6%). Gliomas were the most common tumor category (36%), followed by embryonal tumors (24%) and ependymal tumors (10%). Among gliomas, low-grade astrocytoma (44.4%) and pilocytic astrocytoma (27.8%) were predominant subtypes. Medulloblastoma represented 66.6% of embryonal tumors. Most tumors belonged to lower WHO grades, while all embryonal tumors classified as grade 4. Conclusions: Gliomas were the most frequently encountered pediatric CNS tumors, with a predominance of supratentorial location and male preponderance. Histopathological evaluation remains indispensable for accurate classification and grading, thereby facilitating optimal management and prognostic assessment of pediatric CNS tumors.